The Struggle for Teacher Professionalism in a Mandated Literacy Curriculum - Costello, Marsha; Costello, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
This article reports on a study investigating how elementary teachers experienced the literacy initiatives that have been implemented in schools across PEI over the past five years. Such initiatives included the implementation of standardized instructional and assessment materials across the board and the emphasis on consistency of program use, reporting, and evaluation. Data were gathered through an online survey and interviews. Throughout this study, issues of professionalism, emotional impact, and teacher resistance were explored. This article focuses specifically on the issue of teacher professionalism and its relationship with prescribed curriculum. Findings suggest that professionalism is challenged when teachers attempt to adhere to the fidelity of program processes. However, fidelity to the purpose of a program would allow for teacher decision-making and autonomy within the context of any given program or practice.